Um punhado de flores sobre um pântano atormentado : uma leitura de “Novas poesias”, de Lúcio Cardoso - Paz Filho, Luís Alberto dos Santos (2019)
The present work aims to propose the study of the work “Novas poesias", by Lucio Cardoso, and thus, to investigate the matter of desire in the construction of his poetic discourse, starting out from the idea that it is one of the main motivators for the trajectory of their lyrical selves and that, simultaneously, the construction of the meanings in their poems permeates this semantic field. In addition, in parallel, we seek to study how the rhythm, as an organic manifestation of the human being and the literary work contributes to the production of meanings in the perspectives of poetic subjects. Thus, the desire, as the epicenter of the discursive construction of the lyrical selves, has its basis in Psychoanalysis, Philosophy, and, especially, in Literature, under the demand of a multifaceted sign, which is linked to the notion of identity and, therefore, reconfigures the plane of the ideas of the poem.